(untitled) (World Bulletin of Public Health, 2025)
One prevalent type of urologic tumor that develops from the extremely diverse renal tubule epithelium is renal cell carcinoma (RCC). Clinical management for RCC has changed during the past ten years due to medications that target renal cancer cells. The idea that renal cancer stem cells (CSCs), which were isolated from renal carcinomas, are what cause tumor growth and resistance to traditional chemotherapy and radiation has recently been put forth. This has given rise to treatments that target this aggressive cell population. Characterization of disease subtypes will be precisely informed by the precise identification of renal CSC populations and the entire cell hierarchy. In the end, this will help provide more individualized and focused treatments. Tyrosine kinase inhibitors, mammalian target of rapamycin inhibitors (mTOR), interleukins, CSC marker inhibitors, bone morphogenetic protein2, antibody drug conjugates, and nanomedicine are some of the possible targeted options for renal cancer cells and renal CSCs that we have compiled here. To sum up, targeted therapy for RCC offer fresh avenues for research and clinical study as well as a glimmer of hope for more sophisticated clinical treatment.